PERLINDUNGAN KONSUMEN TERHADAP PEREDARAN MAINAN ANAK-ANAK YANG MEMBAHAYAKAN DIKOTA PEKANBARU - Fazariansyah, Bayu; Ismi, Hayatul; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
As a developing country and island countries such as Indonesiasometimes experience a disruption and obstacles to the smoothness of staterevenues, due to the occurrence of a smuggling crime. It is this form of evil thatimpedes the course of economic development, because a lot of state money is notpicked up by the crime of smuggling. In addition smuggling crime is a latentdanger that threatens the country's economy as well as the survival of a country.As for the purpose of writing this thesis, namely; Firstly, to know the role of CivilServant Investigator of Customs and Excise in handling smuggling case of onionbased on Law number 17 of 2006 concerning Customs in Dumai City Law Area,Second, to know what obstacles are found by Customs Civil Servant Excise inhandling the case of smuggling of shallots in the Dumai City Legal Territory.The type of research is sociological legal research is research that wantto see the correlation between law and society, so as to reveal the effectiveness oflaw enforcement in society. The research was conducted at Dumai City Customsand Excise Inspection and Service Office, while the population and sample werethe whole parties concerned with the problems studied in this study, the datasource used, the primary data and the secondary data, the data collectiontechnique in this study by interview And literature study.From the research result of the problem that the Customs and Excise ofDumai City performs supervision in accordance with Law No. 17 of 2006 onCustoms but on the implementation has not been said maximal because there arestill obstacles of the main things that need attention. First is expected to CivilServant Investigators in realizing their role as law enforcement officers areexpected to always be consistent in handling the act of smuggling of onion interms of Preventif. Therefore it takes better human resources to support theperformance of Customs and Excise, improve the infrastructure facilities ownedby Customs and Excise and increase patrol area to smuggling activities.Secondly, it is also expected to further improve its performance so that smugglingactions can be minimized